Politics and identity in design: An analysis of two contemporary Cairene mosques - Sadek, Leena (AUC Knowledge Fountain, 2018)
Forging a national identity has been an issue many Islamic nations have undergone and struggled with in the wake of a colonial era long established in the third world. The attempts at achieving such a goal have been varied, with many seeking to revive their pre-colonial past under new and modern implications. The success of such attempts has not yet yielded a satisfactory template that can be applied without question in one nation, let alone across the Islamic world. Nonetheless, such a quintessential conundrum has not hindered the building program of many nations, who are still striving to achieve their own building style that is a reflection of their history and national identity. Questions of architectural heritage, what aspects of the history held true to the nations' identity, and which aspects were deliberately to be rejected all held an important role in shaping the end product devised by each nation, and all needed to be digested to fathom the national style they sought so ardently. The mosque in particular emerges as the explicit monument type due to its innately Islamic character. For this reason, this study is concerned with the nature of mosque building in the post-modern globalized commercial city fabric we actively partake in today. To remedy this disconnect and notable gap in their architecture, some nations, such as Turkey, undertook a secular national building program to highlight their modernity. Others took on the task of creating a bridge amongst Islamic nations and establishing communication between them by adopting an architecture that incorporated variant elements from different Islamic cultures, as seen in the Gulf states with their "transnational" mosques, as coined by Kishwar Rizvi. In Egypt, a movement returning to previous eras of glory was attempted with Neo-Mamluk architecture, along with attempts at channeling the long lost Pharaonic heritage, a movement that quickly faded. What, then, does contemporary mosque architecture reflect? What weight does patronage carry in the outcome of the building, and how much does it shape its conception? What of the users and how they participate in this dialogue, if at all? Ultimately, how successful was the mosque in reflecting an Islamic character, as well as being coherent with the nature and aspirations of the society? This thesis will conduct an analysis of two contemporary mosques in Cairo, assessing the impact of Islam on the nature and form of the built environment. The scope of the study of this thesis will be a) the description of two mosques in the area of New Cairo, as it is one of the most rapidly evolving sites of urban landscape in the capital, and b) the analysis of these monuments from the perspectives of the Modernist, Traditionalist, and Regionalist approaches, as well as measuring the buildings' success with regard to serving the community. This will inevitably lead to the formulation of conclusions pertaining to the questions mentioned above. The selected mosques are chosen based on their representation of each of the two dominant divisions who chiefly sponsor building in Cairo today, namely the state (whether the government division of the Ministry of Interior, or the separate entity of the Military), and the private sector.